أثر المساندة الاجتماعية على الصحة والمرض - مقاوسي, كريمة (University of Eloued جامعة الوادي, 2017)
تعد المساندة الاجتماعية متغيرا هاما في الوقاية وتنمية الصحة بجوانبها النفسية والعضوية، حيث أثبتت دراسات علمية وطبية حديثة الفوائد الصحية والوقائية والإنمائية للمساندة الاجتماعية على صحة وسلامة العقل والجسم، وتشير أحدث التقارير الطبية في هذا الشأن أن الأشخاص الذين لا يقيمون علاقات اجتماعية طيبة مع الآخرين ولا يتلقون مساندة اجتماعية هم أكثر عرضة من غيرهم للإصابة باضطرابات فسيولوجية ومشكلات صحية مزمنة Social support is considered as an important variable in prevention and in the healthy development with its psychological and organic aspects, in which scientific and modern medicine studies proved the Healthy preventive And development benefits of social support On the health and safety of the mind and body. Also, in this .the medical reports indicated that people who do not make good social relationship with others and do not receive social support are more to be infected by physiological disorders and chronic healthy problems than others.
The impact of social support on health and disease
مقال بمجلة الدراسات والبحوث الاجتماعية
Keywords: المساندة الإجتماعية، أدوار المساندة الاجتماعية، تأثير المساندة الاجتماعية على الصحة، تأثير المساندة الاجتماعية على الأشخاص المرضى; Social support, Roles of social support, The impact of social support .on health, The impact of social support on sick people